Lifestyle Changes Related to Eating Habits, Physical Activity, and Weight Status During COVID-19 Quarantine in Italy and Some European Countries - Catucci, Arianna; Scognamiglio, Umberto; Rossi, Laura (Frontiers in Nutrition, 2021)
Novel human coronavirus disease (COVID-19), an infectious respiratory disease, has affected more than 50 million people around the world up to November 2020, thereby becoming the fifth documented pandemic since the Spanish flu in 1918. SARS-CoV-2 virus originated in China and evolved for 4 months within the country before becoming a global threat. There is currently no drug approved by the Food and Drug Administration (FDA) for which efficacy on the virus has been proved. Therefore, the only strategy against this virus is to apply measures that are capable of reducing its spread, such as isolation and quarantine, social distancing, community-wide containment, and strict enforcement of hygiene. Quarantine has proved to be effective in combating the spread of the virus; however, it has inevitably led to a radical change in the lives of people. Studies have been conducted in Italy and some European countries to highlight the role that quarantine has played in determining the lifestyle changes both in eating habits and physical activity and their possible correlation with increase in weight. The selection criteria involved answering a questionnaire that included information on the weight status and at least one of the other two aspects: changes in eating habits and/or physical activity during the quarantine period. The results obtained indicate, in general, that the negative effect of quarantine was on eating habits and physical activity. This was based on the observation that there has been an increase in food consumption and a reduction in physical activity with a consequent increase in weight.